2018
DOI: 10.1016/j.molcel.2018.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Tma64/eIF2D, Tma20/MCT-1, and Tma22/DENR Recycle Post-termination 40S Subunits In Vivo

Abstract: The recycling of ribosomal subunits after translation termination is critical for efficient gene expression. Tma64 (eIF2D), Tma20 (MCT-1), and Tma22 (DENR) function as 40S recycling factors in vitro, but it is unknown whether they perform this function in vivo. Ribosome profiling of tma deletion strains revealed 80S ribosomes queued behind the stop codon, consistent with a block in 40S recycling. We found that unrecycled ribosomes could reinitiate translation at AUG codons in the 3' UTR, as evidenced by peaks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
98
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(110 citation statements)
references
References 47 publications
12
98
0
Order By: Relevance
“…However, a very recent study reported that the HCV IRES still works efficiently under conditions of a suppressed eIF2 activity in double knockout cells lacking both eIF2A and eIF2D [191]. If so, this result is more consistent with the option to use only eIF5B for HCV translation initiation under stress conditions ( Figure 5B, left).…”
Section: Use Of Alternative Initiation Factors Under Stress Conditionssupporting
confidence: 57%
See 1 more Smart Citation
“…However, a very recent study reported that the HCV IRES still works efficiently under conditions of a suppressed eIF2 activity in double knockout cells lacking both eIF2A and eIF2D [191]. If so, this result is more consistent with the option to use only eIF5B for HCV translation initiation under stress conditions ( Figure 5B, left).…”
Section: Use Of Alternative Initiation Factors Under Stress Conditionssupporting
confidence: 57%
“…It should be noted that, unlike eIF2A, eIF2D resembles other initiation factors since it contains a domain similar to translation initiation factor eIF1 [183]. Recent work performed with ribosomal profiling indicates that eIF2D is involved in post-termination events, where it promotes ribosome recycling [191]. eIF2D can confer HCV translation initiation as an alternative to eIF2.…”
Section: Use Of Alternative Initiation Factors Under Stress Conditionsmentioning
confidence: 99%
“…Recent reports implicated eIF2D and MCT-1/DENR in re-initiation events downstream of uORFs [52,[134][135][136]. The control of these events by MCT-1/DENR in particular appeared to be important for the control of cell proliferation and protein synthesis in proliferating but not quiescent cells in Drosophila [134].…”
Section: Alternate Initiation Pathways As a Response To Stress And Nomentioning
confidence: 97%
“…This could be ABCE1, a ribosome recycling factor known to participate also at the initiation step (reviewed in [80]), or eIF3, which may be recruited to the termination complex and is known to facilitate at least the regular (in cis) reinitiation (for review, see [81]), or even PABP, which is directly involved in termination (see [82] and references therein), while it also affects eIF4F and eIF4B function at the 5 end (see above). An intriguing possibility is the involvement of recycling/reinitiation factors eIF2D and MCT-1/DENR in CLAR [83,84]. Thus, the reinitiating ribosomes, in contrast to "naïve" (de novo entering) ribosomes, can be already loaded with components necessary for 5' UTR binding, scanning, and start codon selection, providing the relaxed dependence on the scanning factors such as eIF4F/eIF4A.…”
Section: Discussionmentioning
confidence: 99%